Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

If
F
(
x
)
=
f
(
g
(
x
)
)
F
(
x
)
=
f
(
g
(
x
)
)
, where
f
(

3
)
=
2
,

f
'
(

3
)
=
8
,

f
'
(
1
)
=
3
,

g
(
1
)
=

3
,
f
(
-
3
)
=
2
,

f

(
-
3
)
=
8
,

f

(
1
)
=
3
,

g
(
1
)
=
-
3
,
and
g
'
(
1
)
=
4
,
g

(
1
)
=
4
,
find
F
'
(
1
)
F

(
1
)
.

F
'
(
1
)
=
F

(
1
)
=